About decentralized swarms of asynchronous distributed cellular automata using inter-planetary file system’s publish-subscribe experimental implementation - Vincent Manuceau (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
This research describes the simple implementation of asynchronous distributed cellular automata and decentralized swarms of asynchronous distributed cellular automata built on top of inter-planetary file system’s publish-subscribe (IPFS PubSub) experimentation. Various publish-subscribe(PubSub) models are described. As an illustration, two distributed versions and a decentralized swarm version of a 2D elementary cellular automaton are thoroughly detailed to highlight the simplicity of implementation with IPFS and the inner workings of these kinds of cellular automata (CA). Both algorithms were implemented, and experiments were conducted throughout five datacenters of Grid’5000 testbed in France to obtain preliminary performance results in terms of network bandwidth usage. This work is prior to implementing a large-scale decentralized epidemic propagation modeling and prediction system based upon asynchronous distributed cellular automata with application to the current pandemic of SARS-CoV-2 coronavirus disease 2019 (COVID-19).